The Ectopic Expression of Btr2 in Aegilops tauschii Switches the Disarticulation Layer From Above to Below the Rachis Node - Zeng, Xiaoxue; Tagiri, Akemi; Kikuchi, Shinji; Sassa, Hidenori; Komatsuda, Takao (Frontiers in Plant Science, 2020)
Seed dispersal among wild species belonging to the tribe Triticeae is typically achieved by the formation of a brittle rachis. The trait relies on the development of a disarticulation layer, most frequently above the rachis node (resulting in wedge type dispersal units), but in some species below the rachis node (resulting in barrel type dispersal units). The genes responsible for the former type are the complementary pair Btr1 and Btr2, while the genetic basis of the latter type has yet to be determined. Aegilops tauschii forms barrel type dispersal units and previous study showed this species lacked an intact copy of Btr1. Here it has been demonstrated that Ae. tauschii carries two of Btr2; and that Btr2 transcript is present in a region below the rachis node where the abscission zone forms. The implication is that in this species, the Btr2 product is involved in the formation of barrel type dispersal units.